The management of infant developmental needs by community nurses - Part 1: Description of the responsibilities of community nurses with regard to the management of infant developmental needs - R. Leech; N.C. van Wyk; C.J.E. Uys (AOSIS, 2007)
This article is one of two that describes the responsibilities of community nurses, according to their legal scope of practice, with regard to the management of developmental needs of infants in primary health care clinics in South Africa. A subsequent article describes the development of guidelines for the support of community nurses to address the developmental needs of infants 0 - 2 years. While evidence confirms that developmental surveillance should be incorporated into the ongoing health care of the infant, such services are not consistently provided in health care settings and, if provided, the delivery thereof suffers from significant inadequacies. A case study strategy was used to investigate the phenomenon and content analysis utilised to analyze the data. The Transactional Model of Development was selected to interpret the data obtained in the study. Findings of the study show that infant developmental care is not included to its fullest potential in the health care delivered to infants and their families, thereby indicating that community nurses do not meet the standards of the profession with regard to the management of infant developmental needs. Health service managers need to review their commitment and type of support to community nurses, if infant developmental care, as part of community nurses' responsibilities, is to be effective and of high quality. Furthermore, community nurses and other health care professionals must recognize the nature and potential of inter-professional collaboration to ensure positive outcomes for infants with developmental delays and disabilities.